De novo induction of a DNA–histone H3K9 methylation loop on synthetic human repetitive DNA in cultured tobacco cells. (17th March 2023) - Otake, Koichiro; Kugou, Kazuto; Robertlee, Jekson; Ohzeki, Jun‐ichirou; Okazaki, Koei; Hanano, Shigeru; Takahashi, Seiji; Shibata, Daisuke; Masumoto, Hiroshi
SUMMARY: Genetic modifications in plants are crucial tools for fundamental and applied research. Transgene expression usually varies among independent lines or their progeny and is associated with the chromatin structure of the insertion site. Strategies based on understanding how to manipulate the epigenetic state of the inserted gene cassette would help to ensure transgene expression. Here, we report a strategy for chromatin manipulation by the artificial tethering of epigenetic effectors to a synthetic human centromeric repetitive DNA (alphoid DNA) platform in plant Bright‐Yellow‐2 (BY‐2) culture cells. By tethering DNA‐methyltransferase ( Nicotiana tabacum DRM1), we effectively induced DNA methylation and histone methylation (H3K9me2) on the alphoid DNA platform. Tethering of the Arabidopsis SUVH9, which has been reported to lack histone methyltransferase activity, also induced a similar epigenetic state on the alphoid DNA in BY‐2 cells, presumably by activating the RNA‐dependent DNA methylation (RdDM) pathway. Our results emphasize that the interplay between DNA and histone methylation mechanisms is intrinsic to plant cells. We also found that once epigenetic modification states were induced by the tethering of either DRM1 or SUVH9, the modification was maintained even when the direct tethering of the effector was inhibited. Our system enables the analysis of more diverse epigenetic effectors and will help to elucidate the chromatin assembly mechanisms of plant cells. Significance Statement: By tethering DNA‐methyltransferase ( Nicotiana tabacum DRM1), we effectively induced DNA methylation and histone methylation (H3K9me2) on a synthetic human centromeric repetitive DNA (alphoid DNA) platform in tobacco BY‐2 culture cells. The tethering of Arabidopsis SUVH9, which has been reported to lack histone methyltransferase activity in vitro, also induced a similar epigenetic state on the alphoid DNA. Our results emphasize that the interplay between DNA and histone methylation mechanisms is intrinsic to plant cells.